2020
DOI: 10.1177/2048872620925265
|View full text |Cite
|
Sign up to set email alerts
|

The association of diabetes and admission blood glucose with 30-day mortality in patients with acute myocardial infarction complicated by cardiogenic shock

Abstract: Background Cardiogenic shock is the leading cause of death in patients with acute myocardial infarction, with short-term mortality of approximately 50%. Whether diabetes mellitus and high blood glucose levels are associated with mortality in contemporary patients with acute myocardial infarction complicated by cardiogenic shock is inadequately described. Purpose To investigate if diabetes mellitus and high admission blood glucose were associated with 30-day mortality in a large, contemporary population with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…Glucose management is the primary goal of patients with diabetes [ 17 ]. Not only does poor blood glucose control increase the risk of retinal, kidney, and microvascular lesions in diabetic patients [ 18 ], but in patients with acute myocardial infarction, adverse fluctuations in blood glucose could exacerbate coronary artery injury [ 19 ]. In this study, diabetic patients with myocardial infarction were divided equally into three groups according to their HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose management is the primary goal of patients with diabetes [ 17 ]. Not only does poor blood glucose control increase the risk of retinal, kidney, and microvascular lesions in diabetic patients [ 18 ], but in patients with acute myocardial infarction, adverse fluctuations in blood glucose could exacerbate coronary artery injury [ 19 ]. In this study, diabetic patients with myocardial infarction were divided equally into three groups according to their HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…1 AMI patients with DM have a significantly higher mortality than those without diabetes. 2 Many studies have shown a relationship between high blood glucose levels on admission and an increased risk of mortality and poor outcomes after AMI. Studies further verified the association between glucose fluctuation during the phases of AMI and the extent of myocardial salvage.…”
Section: Introductionmentioning
confidence: 99%
“…DM is being present in nearly 30% of AMI cases 1 . AMI patients with DM have a significantly higher mortality than those without diabetes 2 . Many studies have shown a relationship between high blood glucose levels on admission and an increased risk of mortality and poor outcomes after AMI.…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed the data from 15 studies. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Specific steps in the process of selection of articles have been detailed in Figure 1. Included studies had an observational study design (Table 1).…”
Section: Resultsmentioning
confidence: 99%